Digital Transformation in the EdTech Industry in India - Paik, Soumya (Global journal of Business and Integral Security, 2024)
India’s educational technology has been on the rise in the recent past. The main factors that can be linked to this increase include the availability of resources, demand for the technology, and the India’s market size. The study investigates whether the educational technology transformation has taken place in India and the success of this transformation. Elements of EdTech are also investigated and the impact of the resources, technology, and accessibility are also evaluated. In this study, three focus group discussions have been convened consisting of between 7 and 9 participants per group. Surveys have also been delivered to 39 participants drawn from students, educators, EdTech companies, and policy-makers. After the collection of data, cleaning was done to ensure accuracy, completeness, and validity of the data. From the analysis of variance, the null-hypothesis in the study is rejected, indicating that the Educational Technology has occurred in India and has mostly been successful. The study has revealed that the main variables in EdTech include market size, teacher satisfaction, desire for digital learning, student retention, and need to have a competitive edge in the schools. The study also reveals that factors like resources, technology, and accessibility have a strong positive correlation with the efficacy of digital transformation in India. The future of EdTech in India is connected to the innovations like Artificial Intelligence and Machine Learning, Blended learning, online classes, and virtual learning among other innovations.